Serological monitoring of avian influenza and Newcastle disease in the Russian Federation in 2019 - M. A. Volkova; I. A. Chvala; O. S. Osipova; M. A. Kulagina; D. B. Andreychuk; I. A. Chvala (Ветеринария сегодня)
More than 30,000 samples of blood serum from domestic, wild and synanthropic birds from 50 regions of the Russian Federation were submitted to the FGBI “ARRIAH” (Vladimir) Reference Laboratory for Avian Viral Diseases to be tested for avian influenza and Newcastle disease within the framework of monitoring activities conducted by the Rosselkhoznadzor in 2019. As a result of the laboratory diagnosis, antibodies to type A influenza virus were detected in vaccinated chickens from two poultry farms in the Perm and Primorsky Krais (A/N9). The detected antibodies were specific to the haemagglutinin subtype of the vaccine antigen. As for the backyards in the RF Subjects, where scheduled vaccination against avian influenza A/H5 is carried out, a low level of immunity was seen in the Rostov and Astrakhan Oblasts (35 and 44%, respectively) while a high level of immunity was observed in the Republic of Altai, Krasnodar Krai, the Chechen Republic and the Primorsky Krai (69, 78, 80 and 88%, respectively). High seroprevalence of Newcastle disease virus in adult poultry in indoor holdings was associated with mass vaccination against the disease. In broiler chickens, post-vaccination antibodies were observed, on average, in 42% of the studied blood serum samples. Antibodies to the Newcastle disease virus were detected in 39% of samples from backyard chickens. Seroprevalence in wild and synanthropic birds was high. The obtained results suggest that the risk of introduction and spread of avian influenza and Newcastle disease in industrial poultry farms and in backyards remains.